Target surface area effects on hot electron dynamics from high intensity laser–plasma interactions. (15th June 2016) - Zulick, C; Raymond, A; McKelvey, A; Chvykov, V; Maksimchuk, A; Thomas, A G R; Willingale, L; Yanovsky, V; Krushelnick, K
Abstract: Reduced surface area targets were studied using an ultra-high intensity femtosecond laser in order to determine the effect of electron sheath field confinement on electron dynamics. X-ray emission due to energetic electrons was imaged using a K α imaging crystal. Electrons were observed to travel along the surface of wire targets, and were slowed mainly by the induced fields. Targets with reduced surface areas were correlated with increased hot electron densities and proton energies. Hybrid Vlasov–Fokker–Planck simulations demonstrated increased electric sheath field strength in reduced surface area targets.